Effects of Mooring Line with Different Materials on the Dynamic Response of Offshore Floating Wind Turbine - Yushun Lian; Fan Zhong; Jinhai Zheng; Wenxing Chen; Gang Ma; Shan Wang; Solomon C. Yim (Journal of Marine Science and Engineering, 2023)
The influence of mooring systems with lines of different material on the dynamic response of a floating wind turbine is studied using a 5 MW OC4-DeepCwind semi-submersible wind turbine as a representative prototype in this study. Two types of mooring systems were designed using the MoorDyn module in OpenFAST software (v3.1.0): one uses chains, and the other uses a hybrid mooring line composed of chains and high-strength polyethylene (HMPE) ropes. A wind turbine with two types of mooring systems was simulated using the OpenFAST software. The results show that the floating wind turbine moored with the hybrid lines exhibited a larger heave and pitch motion than that moored using chains alone. At the same time, the surge displacement was smaller than that of the wind turbine using chains alone. In terms of mooring line tension, the mean and amplitude values of the hybrid mooring system at the location examined were smaller than those of the chain mooring system. Thus, using HMPE ropes in the mooring system can significantly reduce line loads. In addition, the HMPE ropes used in the floating wind turbine mooring system did not affect the power generation of the wind turbine. This study provides promising support data and observations for applying high-strength polyethylene (HMPE) ropes in mooring systems for floating wind turbines.